1973
DOI: 10.1038/icb.1973.76
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Resistance of Mice Infected With Salmonella Enteritidis 11rx

Abstract: Summary The resistance to Ehrlich ascites tumour transplants in mice immunized with live Salmonella enteritidis 11RX was investigated. In mice still carrying the bacterial infection, the resistance appeared to be attributable to an increase in both the number and the anti‐tumour activity of the peritoneal cells. This activity was demonstrated in vivo run by the rapid removal of tumour cells from the peritoneal cavity and in vitro by the cytolysis of tumour cells. The spleen cells of resistant mice did not poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 2 publications
(3 reference statements)
3
11
0
Order By: Relevance
“…immunised mice has been shown to be due to a rapid removal of tumour cells from the peritoneal cavit}^ beginning within the first few hours after challenge (Ashley and Hardy, 1973). The present finding, that within a day after challenge of IIRX carrier mice with '^^I-labelled EAT cells most of the ^^4 was excreted, demonstrate.s that the tumour cells are killed and not merely resited.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…immunised mice has been shown to be due to a rapid removal of tumour cells from the peritoneal cavit}^ beginning within the first few hours after challenge (Ashley and Hardy, 1973). The present finding, that within a day after challenge of IIRX carrier mice with '^^I-labelled EAT cells most of the ^^4 was excreted, demonstrate.s that the tumour cells are killed and not merely resited.…”
Section: Discussionsupporting
confidence: 61%
“…During the IIRX carrier state the peritoneal eavity contains macrophages with increased bactericidal properties (Rowley et al, 1968) and cells capable of killing EAT cells in vitro (Ashley and Hardy, 1973), although it is not k-nown what role these play in tumour resistance. It is, however, clear that after IIRX immunisation the mice possess a mechanism for rapid tumour cell killing and that, when this capacity has declined, it can be recalled by injection of IIRX antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar anti-tumour activity has been shown to be stimulated in the peritoneal exudate cells of mice following infection with bacteria (Ashley and Hardy, 1973) and parasites (Hibbs, Lambert and Remington, 1972;Keller, 1973Keller, , 1974 and following immunization with unrelated antigens (Evans and Alex-ander, 1 972a). We have also reported that administration of C. parvum inhibits tumour growth in vivo, not only in intact mice but also in T cell deficient mice prepared by thymectomy, whole body irradiation and transplantation of isogeneic bone marrow (Woodruff, Dunbar and Ghaffar, 1973).…”
mentioning
confidence: 66%
“…Tumour resistance of 11 RX-infected mice is associated with the generation of PEC which are tumouricidal in vitro {Ashley and Hardy, 1973). This assay was used to detect the anti-tumour effects of the different bacteria and bacterial preparations in these studies.…”
Section: Generation Of Tumouricidal Pec In Mice Wilh a Primary Bactermentioning
confidence: 99%